2000
DOI: 10.1038/sj.pcan.4500477
|View full text |Cite
|
Sign up to set email alerts
|

Early urodynamic effects of the lipido-sterolic extract of Serenoa repens (Permixon®) in patients with lower urinary tract symptoms due to benign prostatic hyperplasia

Abstract: This prospective, controlled study was undertaken to evaluate the early urodynamic and symptomatic impact of the lipido-sterolic extract of Serenoa repens (Permixon 1 1 ) in the treatment of patients with benign prostatic hyperplasia (BPH).A total of 75 patients, aged 52 ± 78 y with lower urinary tract symptoms due to mild/moderate BPH (mean International Prostate Symptom Score (I-PSS) 8.2) were included in the study, of which 57 received Permixon 1 1 160 mg twice daily for 9 weeks. Urodynamic evaluation, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 14 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…Data for meta‐analysis were extracted from a total of 27 studies, of which 15 were RCTs and 12 were observational studies. The selected studies included 5 800 patients corresponding to: Permixon ( n = 3 926); α‐blockers ( n = 775; tamsulosin [ n = 377], unspecified [ n = 398]); 5ARIs ( n = 578; finasteride [ n = 484], unspecified [ n = 94]); placebo ( n = 301); control group ( n = 190); and gestonorone caproate ( n = 30).…”
Section: Resultsmentioning
confidence: 99%
“…Data for meta‐analysis were extracted from a total of 27 studies, of which 15 were RCTs and 12 were observational studies. The selected studies included 5 800 patients corresponding to: Permixon ( n = 3 926); α‐blockers ( n = 775; tamsulosin [ n = 377], unspecified [ n = 398]); 5ARIs ( n = 578; finasteride [ n = 484], unspecified [ n = 94]); placebo ( n = 301); control group ( n = 190); and gestonorone caproate ( n = 30).…”
Section: Resultsmentioning
confidence: 99%
“…There are numerous clinical studies performed with S. repens. Al-Shukri et al [12] described an improvement in IPSS, QoL and urinary flow rate. A six-month study illustrated that S. repens extracts led to a statistically significant improvement in urinary symptoms in men with lower urinary tract problems compared with placebo, however with no measurable effect on the urinary flow rates or sexual life as compared with placebo [13].…”
Section: Armentioning
confidence: 98%
“…For example, an open-label study performed on 50 patients treated with Serenoa repens for 6 months, showed an improvement of symptoms but found no significant effect in other parameters such as flow rate and bladder pressure [39] showing a significant placebo-effect in symptom perception. In contrast, another study of 75 patients treated with Permixon ® (lipidosterolic Serenoa repens extract) found a significant improvement in urodynamic parameters in comparison to placebo [40].…”
Section: Serenoa Repens (Saw Palmetto)mentioning
confidence: 89%